Towards Financial Inclusion: An Assessment for Suriname - Nancy Fraser; Cherique MacDonald; Gavin Ooft (Centrale Bank van Suriname, 2019)
This paper presents an assessment of financial inclusion in Suriname, mainly from the Central Bank's perspective. It examines existing data on financial inclusion and policy initiatives and measures the Central Bank of Suriname has taken to stimulate financial inclusion. This research is mainly conducted through desk studies and is supported by interviews with various stakeholders involved with financial inclusion and education as well as with the relevant Central Bank departments in charge of national financial inclusion initiatives. Consequently, the study presents policy recommendations aimed at improving financial inclusion in Suriname, since it is an important contributor to monetary policy and a prerequisite for financial stability.
Additional information: The authors are staff members of the Central Bank of Suriname. The views expressed in this paper are those of the authors and do not necessarily reflect those of the Bank. Research papers are work in progress and are published to elicit comments for further debate.
Keywords: G29; G53; O16; E44; 330; Financial Inclusion; Financial Services; Financial Literacy; Monetary Policy